Pengaruh E-WOM, Brand Image, dan Brand Love Terhadap Brand Loyalty dengan Brand Trust Sebagai Variabel Intervening pada dua Merek Air Minum Terpopuler di Soloraya - Ardy Wijaya; Moechammad Nasir (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze and compare the influence of electronic word of mouth (e-WOM), Brand Image, and Brand Love on Brand Loyalty with Brand Trust as a mediating variable in AQUA and Lee Minerale brands in Solo Raya. This research is an explanatory research with a quantitative approach. Data were collected from 400 respondents, consisting of 200 AQUA consumers and 200 Lee Minerale consumers, selected using purposive sampling technique. The research instrument used a five-point Likert scale. Data were analyzed using Partial Least Squares (PLS) with SmartPLS software. The results show that for both brands, e-WOM, Brand Image, and Brand Love have a significant positive effect on Brand Trust and Brand Loyalty. In addition, Brand Trust is proven to fully mediate the influence of e-WOM, Brand Image, and Brand Love on Brand Loyalty for both AQUA and Lee Minerale. These findings indicate that building Brand Trust is an important strategy in increasing consumer loyalty in the bottled drinking water industry.